ZOONOTIC tuberculosis : mycobacterium bovis and other pathogenic mycobacteria / editor Charles O. Thoen, James H. Steele, John B. Kaneene. - Thoen, Charles O; Steele, James H. (Wiley Blackwell, 2014)
xvii, 413 hlm. : ilus. ; 25 cm